PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN KEPEMILIKAN SAHAM PUBLIK TERHADAP LUAS PENGUNGKAPAN CSR PADA PERUSAHAAN DI SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2014-2015 - Hanavistha Nadya Kusuma (Jurnal Ilmiah Mahasiswa FEB, 2016)
The study aims to examine the effect of company size, leverage, and public shareholding on the disclosure of corporate social responsibility. The research samples, which comprise of 36 companies of mining sector listed in the  Indonesia  Stock Exchange  in  2014-2015,  are  selected  by purposive sampling method. The type of data used is secondary data, and they are analyzed through multiple regression method to determine the effects of the variables.  The  results  of  the  study show  that company size  and  public shareholding have significant effect on corporate social responsibility disclosure. The larger the size of a company, the wider the corporate social responsibility the company will disclose. Meanwhile, leverage does not affect the corporate social responsibility disclosure. This shows that companies in the mining sector in Indonesia do not pay attention to the company’s leverage level in disclosing their corporate social responsibility.Keywords: Corporate Social responsibility, Company size, Leverage, Public Shareholding